Nuevos registros de macromicetes de Colombia i. Macromicetes recolectados en zonas urbanas de Medellín (Antioquia) (2011)
ABSTRACT: During an eleven year period, carpophores of macrofungi growing on the campus of the Universidad de Antioquia (Medellín), Colombia were collected. A total of 42 collections yielded 28 species, of which 26 species were distributed in 22 genera, 10 families and 3 orders of the Basidiomycota; the other two species belonged to the genus Xylaria, (Xylariaceae, Xylariales) in the Ascomycota. Eight species are reported for the first time from the country and six are new records for the Antioquia department. Distribution data are included for the species listed. Key words: Ascomycota, Basidiomycota, macrofungal diversity, new records, urban environments.